2015
DOI: 10.1152/ajpheart.00528.2014
|View full text |Cite
|
Sign up to set email alerts
|

The functional effect of dilated cardiomyopathy mutation (R144W) in mouse cardiac troponin T is differently affected by α- and β-myosin heavy chain isoforms

Abstract: Given the differential impact of α- and β-myosin heavy chain (MHC) isoforms on how troponin T (TnT) modulates contractile dynamics, we hypothesized that the effects of dilated cardiomyopathy (DCM) mutations in TnT would be altered differently by α- and β-MHC. We characterized dynamic contractile features of normal (α-MHC) and transgenic (β-MHC) mouse cardiac muscle fibers reconstituted with a mouse TnT analog (TnTR144W) of the human DCM R141W mutation. TnTR144W did not alter maximal tension but attenuated myof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 52 publications
5
37
0
Order By: Relevance
“…Previously, we demonstrated that the level of β-MHC expression is ~70% of the total MHC in TG mouse hearts [11]. Moreover, β-MHC expression did not alter the stoichiometry or the phosphorylation status of other sarcomeric proteins [11].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, we demonstrated that the level of β-MHC expression is ~70% of the total MHC in TG mouse hearts [11]. Moreover, β-MHC expression did not alter the stoichiometry or the phosphorylation status of other sarcomeric proteins [11].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, β-MHC expression did not alter the stoichiometry or the phosphorylation status of other sarcomeric proteins [11]. c - myc tagged TnT and the endogenous TnT migrated differently on the SDS gel.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations